2004
DOI: 10.1590/s1020-49892004001100001
|View full text |Cite
|
Sign up to set email alerts
|

Evolución de la mortalidad por enfermedad isquémica del corazón e infarto agudo del miocardio en Costa Rica, 1970-2001

Abstract: A reduction in mortality from CVD was noted. The largest rates were seen among men and in persons 75 years of age or older. The largest increases in mortality rates from IHD and AMI were seen in semi-urban and rural areas, among men, and in persons 75 years of age or older. Special attention should be paid to risk factors for CVD, such as smoking, arterial hypertension, overweight and obesity, sedentary habits, and an unhealthy diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
3
5
0
4
Order By: Relevance
“…The above information allows us knowing that, in all quinquennia comprised within the 1970-1974 and 2010-2014 periods, IHD rates were higher in men in comparison with women, with the ratio being lower at the beginning of the series (1.43:1) and higher at the end of it (2.23:1). In addition, the ratio in favor of males is observed to gradually increase throughout all quinquennia, a result that is consistent with another study conducted in the country 11 , in addition to results obtained in other nations, such as Mexico 24,25 . Life expectancy in Costa Rica has always been higher in women in comparison with men (82.2 years for women and 77.5 for men, year 2016), which would partly explain the above observation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The above information allows us knowing that, in all quinquennia comprised within the 1970-1974 and 2010-2014 periods, IHD rates were higher in men in comparison with women, with the ratio being lower at the beginning of the series (1.43:1) and higher at the end of it (2.23:1). In addition, the ratio in favor of males is observed to gradually increase throughout all quinquennia, a result that is consistent with another study conducted in the country 11 , in addition to results obtained in other nations, such as Mexico 24,25 . Life expectancy in Costa Rica has always been higher in women in comparison with men (82.2 years for women and 77.5 for men, year 2016), which would partly explain the above observation.…”
Section: Discussionsupporting
confidence: 91%
“…Roselló and Guzman 10 analyzed mortality during the 1970-2002 period according to its geographical distribution and place of occurrence. Subsequently, these two researchers published another article on the same subject, in this case with greater extension and depth, since they also included CVD, IHD and AMI mortality evolution during the 1970-2001 period 11 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we found that students from public universities reported being afraid of becoming infected with HIV while caring for PLHWA and preferred to care for non-HIV patients instead ( Table 4 , items 4 and 9). Similar findings of such fears and preferences have been documented elsewhere among medical students and healthcare workers [ 13 , 18 , 37 , 38 ]. These attitudes have been largely attributed to cases of HIV transmission via needle prick injury sustained during the course of caring for PLHWA [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 85%
“…French fries, potato chips, and mashed potatoes are part of the Western dietary pattern, which is also high in red meats, processed meats, and refined flours [ 21 , 22 ]. In contrast, the consumption of starchy vegetables in Costa Rica is likely associated with a healthier dietary pattern predominantly relying on fresh vegetables, cereals, and legumes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%